2013
DOI: 10.1016/j.chembiol.2012.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effector Kinase Coupling Enables High-Throughput Screens for Direct HIV-1 Nef Antagonists with Antiretroviral Activity

Abstract: HIV-1 Nef, a critical AIDS progression factor, represents an important target protein for antiretroviral drug discovery. Because Nef lacks intrinsic enzymatic activity, we developed an assay that couples Nef to the activation of Hck, a Src-family member and Nef effector protein. Using this assay, we screened a large, diverse chemical library and identified small molecules that block Nef-dependent Hck activity with low micromolar potency. Of these, a diphenylpyrazolo compound demonstrated sub-micromolar potency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
120
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(130 citation statements)
references
References 40 publications
10
120
0
Order By: Relevance
“…Previous studies have shown that, unlike WT HIV-1 NL4-3, infectivity and replication of the ΔNef mutant are unaffected by Nef inhibitor treatment (29)(30)(31). Coculture of ex vivo autologous CD8 T cells (n = 6) or HIV-1 peptide-expanded CD8 T cells (n = 10-11) with these NL4-3 ΔNef latently infected CD4 T cells did not result in a significant difference between control and either of the Nef inhibitor-treated samples, as reflected in Figure 3, G and H. Of interest is that baseline levels of IFN-γ in the no inhibitor cocultures with expanded CD8 T cells were elevated if resting CD4 T cells were infected with Nef-deficient virus relative to targets that were infected with Nef-competent virus (median 179.3 pg/ ml vs. 119.1 pg/ml, respectively), supporting the role of Nef in preventing recognition of latently infected cells.…”
Section: Experimental Overview and Generation Of Latently Hiv-1-infecmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have shown that, unlike WT HIV-1 NL4-3, infectivity and replication of the ΔNef mutant are unaffected by Nef inhibitor treatment (29)(30)(31). Coculture of ex vivo autologous CD8 T cells (n = 6) or HIV-1 peptide-expanded CD8 T cells (n = 10-11) with these NL4-3 ΔNef latently infected CD4 T cells did not result in a significant difference between control and either of the Nef inhibitor-treated samples, as reflected in Figure 3, G and H. Of interest is that baseline levels of IFN-γ in the no inhibitor cocultures with expanded CD8 T cells were elevated if resting CD4 T cells were infected with Nef-deficient virus relative to targets that were infected with Nef-competent virus (median 179.3 pg/ ml vs. 119.1 pg/ml, respectively), supporting the role of Nef in preventing recognition of latently infected cells.…”
Section: Experimental Overview and Generation Of Latently Hiv-1-infecmentioning
confidence: 98%
“…To test this hypothesis, we employed the use of small molecule inhibitors previously shown to bind HIV-1 Nef directly and block its functions related to HIV-1 infectivity and replication enhancement (29)(30)(31). The structures of the 4 inhibitors used in this study are shown in Supplemental Figure 1 (supplemental material available online with this article; https://doi.org/10.1172/jci.insight.93684DS1).…”
Section: Experimental Overview and Generation Of Latently Hiv-1-infecmentioning
confidence: 99%
See 2 more Smart Citations
“…Nef-dependent activation of Hck contributes to HIV-1 replication, in that selective inhibitors of this pathway interfere with viral replication in vitro. [42][43][44] More recent studies have suggested a similar role for the Tec-family kinase Itk in HIV-1 pathogenicity as well, although the connection between the virus and Itk were not initially apparent. 45 Subsequent cell-based bimolecular fluorescence complementation (BiFC) assays revealed selective interaction of HIV-1 Nef with the Tecfamily kinases Itk, Btk, and Bmx.…”
mentioning
confidence: 99%